Pedagogical Opportunities for Developing Creative Thinking in Visual Arts Lessons - Gadoyev Ibrohim Niyozovich (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article analyzes the pedagogical possibilities of developing students’ creative thinking in visual arts lessons. Various didactic methods, interactive techniques, and practical exercises are discussed to enhance students’ artistic cognition. The article highlights methods for stimulating creativity, analyzing artworks, and creating original artistic works, focusing on the development of independent and innovative thinking skills.